If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7m + 13 = 14m Reorder the terms: 13 + -7m = 14m Solving 13 + -7m = 14m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-14m' to each side of the equation. 13 + -7m + -14m = 14m + -14m Combine like terms: -7m + -14m = -21m 13 + -21m = 14m + -14m Combine like terms: 14m + -14m = 0 13 + -21m = 0 Add '-13' to each side of the equation. 13 + -13 + -21m = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -21m = 0 + -13 -21m = 0 + -13 Combine like terms: 0 + -13 = -13 -21m = -13 Divide each side by '-21'. m = 0.619047619 Simplifying m = 0.619047619
| 3x-87=33-5x | | 2x=6-8x | | (u+3)*7=16 | | -6=d/18 | | C=(3.14)r | | (x^2)+3z=0 | | 24+m=-93 | | -10x-143=7x+78 | | 32=18 | | x+2=-4-2x | | (x+4)(2x+2)= | | x^2-2x+400=0 | | 25=5+.50x | | (q-3)*2=16 | | 12x-31=38+9x | | 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x | | 79x^2-200x+125=0 | | x+7+3x=13+x | | 6(a-3)= | | 45-33x+33-44x=-45+33x-33+44x | | 11x-11=7x+12 | | 4j+4=6 | | 6y-5=3+4y |